'A qualitative investigation into the impact of domestic abuse on women's desistance': A practitioner's response. (December 2020) - Reed, Rachel
This article is a response to Barr and Christian's article 'A qualitative investigation into the impact of domestic abuse on women's desistance'. Based on the findings of two separate but interlinked projects considering women's qualitative desistance experiences in the community, Barr and Christian argue for a reframing of desistance from crime as desistance from harm when working with women in the criminal justice system. This article seeks to consider this reframing in terms of probation practice and contemplates some of the structural and cultural barriers which may currently stand in the way.